The meanings and possible implications of critical Islamic religious education. Issue 2 (3rd April 2021) - Saada, Najwan; Magadlah, Haneen
ABSTRACT: The teaching of Islam in Western and non-Western societies may be located along a continuum from critical to non-critical paradigms. Islamic religious education is dominated by the non-critical paradigm and a devotional discourse of religious education. This is true in both Islamic and non-Islamic countries and is relevant to the teaching of both the spiritual and moral messages of Islam. The current essay is motivated by the 'inadequate theoretical reflections on the meaning of education, which gravely hinder the task of thinking about Islam educationally and education Islamically'. The first section reviews the tenets of Islamic religious education from a conservative and devotional perspective. In the second and third sections, the authors address the major shortcomings of this approach and its theory of Islamisation. In the final section, the authors propose a rationale for an alternative paradigm of critical Islamic religious education – which is rarely discussed in the literature – and for its appropriateness for living in modern, democratic, multi-faith societies.